Survival in Duchenne muscular dystrophy in Australia: a 50 year retrospective cohort studyResearch in context - Zoe E. Davidson; Suzanna Vidmar; Amanda Griffiths; Mark E. Howard; David J. Berlowitz; Elizabeth F. Jones; Tim Scully; Darran Treanor; Bikram Singh; David Prior; Matilde G. Frost; Robin Forbes; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: There is limited evidence describing the changing natural history of DMD in Australia. Methods: This retrospective cohort study collated information on clinical management and disease milestones from medical records of males with DMD attending a paediatric hospital between 1973 and 2019 and linked this to information from two adult tertiary hospitals. Data were stratified by decade of birth and Kaplan Meier analyses were conducted to describe median time to key disease milestones. Findings: The cohort included 356 individuals with DMD with year of birth ranging from 1958 to 2014 and median (interquartile range, IQR) follow up time from diagnosis of 10.5 (4.1, 15.7) years. Use of corticosteroids, angiotensin-converting enzyme inhibitors (ACE-I), echocardiography and respiratory support increased over time. Mean age of diagnosis decreased from 6.4 years in those born before 1970 to 3.4 years in those born 2010–2019. Median (IQR) survival increased over time from 18.2 (15.2, 20.4) years in those born before 1970 to 24.0 (20.3, 27.5) years in those born between 1990 and 1999. Increased life expectancy was observed in individuals using corticosteroids, ACE-I and respiratory support. Interpretation: Survival in individuals with DMD has increased over the last five decades, likely due to changes in clinical management. Given the increased population surviving to adulthood, there is a need to enhance clinical services and surveillance to support neuromuscular disease in Australia, especially in transitional care and adult populations. Funding: Independent Research Grant, Pfizer Australia.